Krüppel-associated boxes are potent transcriptional repression domains. - Margolin, J F (1994)
The Krüppel-associated box (KRAB) is a highly conserved, 75-aa region containing two predicted amphipathic alpha-helices. The KRAB domain is present in the amino-terminal regions of more than one-third of all Krüppel-class Cys2His2 zinc finger proteins and is conserved from yeast to man; however, its function is unknown. Here it is shown that the KRAB domain functions as a DNA binding-dependent transcriptional repressor when fused to a heterologous DNA-binding domain from the yeast GAL4 protein. A 45-aa segment containing one of the predicted KRAB amphipathic helices was necessary and sufficient for repression. Amino acid substitutions in the predicted helix abolished the repression function. These results assign a function, transcriptional repression, to the highly conserved KRAB box and define a minimal repression domain which may aid in identifying mechanisms of repression.